VizieR Online Data Catalog: NGC1326A, 1425 and 4548 supergiants VI mags (Spetsieri+, 2019) - Spetsieri, Z. T.; Bonanos, A. Z.; Yang, M.; Kourniotis, M.; Hatzidimitriou, D. (2019)
We used archival observations of NGC 1326A, NGC 1425, and NGC 4548 taken with the HST WFPC2 as described in Freedman et al. (2001ApJ...553...47F) as part of the HST Key Project. For the three galaxies, we used the observations available in the filters F555W(equivalent to Johnson V filter) and the F814W (equivalent toKron-Cousins I). In particular, we used 13 epochs of observations in F555W and 8 epochs in F814W that are available for the galaxies NGC 1326A and NGC 4548, while for NGC 1425, we used the 14 available epochs in F555W and 8 in F814W (6 data files).
Keywords: Galaxies: nearby; Photometry: HST; Stars: supergiant; Stars: variable